Overlying Strata Movement Laws Induced by Longwall Mining of Deep Buried Coal Seam with Superhigh-Water Material Backfilling Technology - Fangtian Wang; Qi Ma; Gang Li; Chengguo Wu; Guangli Guo (Advances in Civil Engineering)
The “Three Under Mining” (mining under the buildings, the railways, and the waters) coal resources are stored in the central and eastern China. Many large-scale mine disasters occurred due to overburden strata movement and surface subsidence. Longwall mining with superhigh-water material backfilling technology has been improved efficiently to prevent the underground disasters and protect the surface ecological environment. Since underground mine pressure behavior and overlying strata movement are influenced by the backfilling strength and backfilling rates, rational design of backfilling parameters is key to realize the green mining of deep buried coal seams. Based on the combination of geological and production conditions of a deep buried coal seam with composite beam theory, the roof fracture distance was analyzed. The software of UDEC was used to simulate the overlying strata movement laws affected by the different backfilling strength and backfilling rates. With the comparative analysis of the vertical displacement movements and the vertical stress distributions, the reasonable filling rate and water volume fraction were determined to be 90% and 95%, respectively. According to the field experiments, the underground dynamic load was low enough for the safe mining, and the village building can be kept in a stable state with the application of the backfilling technology. The research results in a scientific basis for the coordinated development between the safe and efficient mining of deep buried coal resources and protection of the surface ecological environment.